Resilience Portfolios and Poly-Strengths: Identifying Strengths Associated with Wellbeing after Adversity - Moisan, Caroline; Hébert, Martine; Fernet, Mylène; Blais, Martin; Amédée, Laetitia Mélissande (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2019)
Objectives: This study aimed to describe the prevalence of traumas and strengths in a representative sample of Quebec youth and to test whether poly-strengths were associated with low psychological distress, after controlling for poly-traumas. Method: Using data from the Quebec Youths’ Romantic Relationships survey (QYRRS), hierarchical logistic regressions were conducted to examine the relationship between poly-strengths and low levels of psychological distress, and to identify which strengths were associated with outcomes, after accounting for demographic variables and individuals’ experiences of traumas. Results: More than a third of the sample experienced 4 traumas or more (37.0%). The average number of experienced traumas was 3.04 out of 10 measured traumas. More than half of the sample had at least 5 strengths, the average number of strengths being 3.95 (out of 8). Two third (67.6%) of the sample did not suffer from psychological distress. Among poly-victims, half of the participants (49.6%) showed clinical symptoms of distress. Poly-strengths were uniquely associated with low of clinical distress. After accounting for demographics and poly-traumas, poly-strengths explained 24.2% of the variance of low levels of psychological distress. Self-esteem, optimism, parental support and attachment, number of sources of support, social support (seeking secure base), and capacity to adapt (resiliency) were uniquely associated with low levels of distress. Conclusion and Implications: The combination of strengths decreases the likelihood of experiencing clinical levels of psychological distress, which can contribute to healthy functioning in context of adversities. Findings highlight the importance of promoting multiple and diverse strengths among youth.